2006
DOI: 10.1186/bcr1608
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression signatures of morphologically normal breast tissue identify basal-like tumors

Abstract: Introduction The role of the cellular microenvironment in breast tumorigenesis has become an important research area. However, little is known about gene expression in histologically normal tissue adjacent to breast tumor, if this is influenced by the tumor, and how this compares with non-tumor-bearing breast tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(146 citation statements)
references
References 52 publications
5
134
2
1
Order By: Relevance
“…37 We also could not discern differences between CN and RM by unsupervised hierarchical clustering or principal component analysis of all genes (results not shown). This may be due to the presence of genes that vary from patient to patient and obscure the consistent differences between CN and RM that we see when comparing directly these 2 sample types.…”
Section: Discussionmentioning
confidence: 99%
“…37 We also could not discern differences between CN and RM by unsupervised hierarchical clustering or principal component analysis of all genes (results not shown). This may be due to the presence of genes that vary from patient to patient and obscure the consistent differences between CN and RM that we see when comparing directly these 2 sample types.…”
Section: Discussionmentioning
confidence: 99%
“…Immune--enriched stromal tissue shows significantly greater activation of the signature (p--vlaue=8.99x10 --4 ), while the epithelial tissue does not (p--value=0.560). Expression data was obtained from [15]; the signature was obtained from [16]. [13,18], while signatures were obtained from [19--21].…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al [1] and Finak et al [2] ranked genes using a measure related to the t-statistic that is computed as part of significance analysis of microarrays (SAMs) [5]. Chang et al [3] reported "selection for genes that were concordantly induced or repressed" which may be accounting for variability because the probability of concordance depends on both signal and noise.…”
Section: Identifying Differentially Expressed Genesmentioning
confidence: 99%
“…Finak et al [2] used microarrays to investigate gene expression in four types of histologically normal cells in 66 samples from 44 patients, 25 samples from epithelial duct cells adjacent to breast cancer, 26 samples from stromal cells adjacent to breast cancer, 9 samples from epithelial duct cells in patients undergoing cosmetic breast reduction surgery, and 6 samples from stromal cells in patients undergoing cosmetic breast reduction surgery. A cluster analysis on all genes and on 883 genes differentially expressed between stroma and epithelial tissue indicated that epithelium versus stroma, and not type of patient, was the dominant explanation for the clustering.…”
Section: Breast Stroma and Epithelial Cells In Breast Cancer Patientsmentioning
confidence: 99%